2009
DOI: 10.1177/0959683609345076
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoclimatic indicators in soils buried under archaeological monuments in the Eurasian steppe: a review

Abstract: The Russian experience of the local reconstruction of the Eurasian steppe climate during the last 5000 years based on geoarchaeological approaches is reviewed. Examples of traditional palaeoclimatic reconstructions in Russia based on organic matter, highly soluble salts and gypsum content and location of salts and gypsum horizons in the profile of buried soils are given. Pedogenic carbonate as a palaeoclimatic indicator is considered. The possibilities of the quantitative reconstruction of the palaeoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It is now 40 years ago that Seaward et al [38] first suggested that it may be possible to utilize qualitative and quantitative analyses, based on the incidence/abundances of microbial taxa with specific environmental requirements, for archaeological interpretation. Nevertheless, Seaward's prognosis has still not become a reality for now, and the study of soil microorganisms has not been routinely incorporated into the archaeologist's toolkit for the reconstruction of human-environment in historical periods [13]. In the current investigation, using DNA-based high-throughput sequencing, we present here the first example of the qualitative and quantitative microbial analyses of a palaeosol for historical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now 40 years ago that Seaward et al [38] first suggested that it may be possible to utilize qualitative and quantitative analyses, based on the incidence/abundances of microbial taxa with specific environmental requirements, for archaeological interpretation. Nevertheless, Seaward's prognosis has still not become a reality for now, and the study of soil microorganisms has not been routinely incorporated into the archaeologist's toolkit for the reconstruction of human-environment in historical periods [13]. In the current investigation, using DNA-based high-throughput sequencing, we present here the first example of the qualitative and quantitative microbial analyses of a palaeosol for historical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive historical reconstruction generally requires multiple proxies and more archaeological evidence can add illumi-nating details [13]. There is another important but generally underestimated facet of archaeological interpretation, which is the associated microbial communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, in the advanced geoarchaeology literature, much attention has been paid to the study of buried soils (see the review by Mitusov et al [26]); while the daylight soils of archaeological sites have not been studied in depth. However, about 40 years ago, Gladfelter [27] stressed the prospects for geoarchaeological elaboration of approaches for differentiating cultural and natural features, including post-occupational disturbances by biological and pedological processes.…”
Section: Approaches and Methods For Determining T-values Formulas Authormentioning
confidence: 99%
“…Archeobotanical evidence for pulses appears lacking in the Steppes when archeobotanical sites with recovery of pulses are mapped (Mikić, 2012, 2015a, 2016; Mikić et al, 2014). One possible explanation for archeological recovery of remains of cereals in the Steppes, but not of pulses, is that Bronze Age Steppes were semiarid, as indicated by paleoclimatic studies (Alekseeva et al, 2007; Khomutova et al, 2007; Mitusov et al, 2009). Estimates of mean annual precipitation imply climate may have been unsuitable for consistent cultivation of legumes, but typically with sufficient moisture for cereals (Dugan, 2015).…”
mentioning
confidence: 99%